Teaching Strategy of Intensive English Course at Language Center of IAIN Samarinda - Nurcahyani, Diah; Bahrani, Bahrani (Borneo Journal of Language and Education, 2021)
In the learning process, a teacher must have a strategy in any subject including English lesson. Why the lecturer must have strategy in teaching, because strategy can support the learning process and achieve the learning goals. The strategy used by lecturer in teaching English will make the students more enjoy of the learning process because in the class the students have different abilities in understanding English lesson. The aim of this research is to analyzed lecturer’s strategies in teaching English at class of Intensive English Course of Language Center IAIN Samarinda 2019/2020. The researcher used qualitative research design. The subject of this research was one English lecturer of English Course at Language Center IAIN Samarinda. The data were gotten from interview. Then the data would be analyzed by reduction, display and conclusion. The result of this research showed that the lecturer’s strategies in teaching English as follows: (1) The lecturer prepared the Lesson Plan (RPS) before teaching English. Lesson Plan has an important role to improving the quality of education. (2) In giving materials the lecturer was not only use text book but also used article and internet. (3) The methods used by teacher in teaching English were Grammar Translation Method. (4) The media used by lecturer in teaching English were Visual. (5) In classroom the lecturer build the good interaction with the students and helped the students who have difficult in the lesson. (6) The lecturer used oral and written test and also his own assessment to student every two weeks. (7) The lecturers gave reinforcement to the students in the last of lesson by giving motivation to always improve study in English and ask the students that still not understand about the lesson to consult with the lecturer and asked the students to review again the material that has been learned at home.